2015
DOI: 10.1002/chem.201503490
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Copper(III) Corrole as an Electron Acceptor: Photoinduced Charge Separation in Zinc Porphyrin–Copper Corrole Donor–Acceptor Conjugates

Abstract: An electron-deficient copper(III) corrole was utilized for the construction of donor-acceptor conjugates with zinc(II) porphyrin (ZnP) as a singlet excited state electron donor, and the occurrence of photoinduced charge separation was demonstrated by using transient pump-probe spectroscopic techniques. In these conjugates, the number of copper corrole units was varied from 1 to 2 or 4 units while maintaining a single ZnP entity to observe the effect of corrole multiplicity in facilitating the charge-separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 87 publications
3
30
0
Order By: Relevance
“…Here we demonstrate the utility of the AT-CuAAC reaction in the synthesis of mechanically interlocked analogues of previously studied triazole-linked porphyrin–corrole conjugates, 21 and that, because the covalent structure of the chromophores is not altered, photo-induced electron transfer between the tetrapyrrole chromophores is unaffected by mechanical bond formation. 22 Conversely, the threaded macrocycles significantly modify the steric properties of the system, creating a “mechanical picket fence” motif that suppresses aggregation and ligand driven self-assembly.…”
Section: Introductionmentioning
confidence: 75%
“…Here we demonstrate the utility of the AT-CuAAC reaction in the synthesis of mechanically interlocked analogues of previously studied triazole-linked porphyrin–corrole conjugates, 21 and that, because the covalent structure of the chromophores is not altered, photo-induced electron transfer between the tetrapyrrole chromophores is unaffected by mechanical bond formation. 22 Conversely, the threaded macrocycles significantly modify the steric properties of the system, creating a “mechanical picket fence” motif that suppresses aggregation and ligand driven self-assembly.…”
Section: Introductionmentioning
confidence: 75%
“…Among the different strategies used in the functionalization/post-functionalization of easily available corroles to obtain target molecules, the CuAAC approach is being successfully used. New corrole derivatives linked to other corroles [124], to porphyrins [125,126] and to BODIPYs [127] were successfully obtained, as recently reviewed by some of us [123]. In this section, only a few publications are being considered to illustrate the impact of the CuAAC approach in the functionalization of corroles.…”
Section: Corrole Macrocyclesmentioning
confidence: 99%
“…The first studies on the synthesis of multichromophores were based on obtaining multiporphyrin arrays [ 7 – 9 ] that could stabilize only metal ions in a bivalent state. To overcome this limitation, porphyrin conjugates with different chromophore groups such as fullerene [ 10 12 ], BODIPY [ 13 15 ], corrole [ 16 – 23 ], phthalocyanine [ 24 26 ], subporphyrin [ 27 ] and expanded porphyrins [ 28 30 ] were prepared and their photophysical and electrochemical properties were characterized. Among these compounds, corroles, contracted porphyrin analogues [ 31 33 ], assumed an important place in porphyrin chemistry due to their small cavities, trianionic characters, high fluorescence quantum yields and favorable electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Porphyrin–corrole conjugates have been successfully used as donor–acceptor systems in photoinduced charge separation processes. It was shown that derivatives of these conjugates could be potentially used in photovoltaic applications [ 21 23 ]. In order to achieve rapid energy and electron transfer between macrocycles, the short distance between subunits keeps an important place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation